Information structure : the syntax-discourse interface - Erteschik-Shir, Nomi (Oxford linguistics., 2007)
This introduction to information structure discusses a wide range of phenomena on the syntax-information structure interface. It examines whether information structure maps onto syntax, and if so how. The topics covered include definitions of topic and focus, architectures of grammar, information structure, word order, the lexicon and information structure interface, and cognitive aspects of information structure. This book will appeal to graduate students of syntax and semantics in. departments of linguistics, philosophy, and cognitive science. - ;This introduction to the role of information.